University proceedings. Volga region. Social sciences - E.V. Bityutskiy; N.I. Svechnikov (Известия высших учебных заведений. Поволжский регион: Общественные науки)
Background. The relevance of the problem under study is that the problems asso-ciated with the qualification and proof in cases of illegal drug production often arise due to different interpretations of the provisions of criminal law. It is important to note that for the correct qualification of such crimes, it is necessary to take into account the entire set of circumstances of each specific criminal event, as well as the presence of intent on the part of the person to commit them and other facts. The formation of an evidence base for such criminal cases can also present a number of issues. In this regard, it is important to ensure the legality from the moment of seizure of objects, substances and documents until the moment of resolving the issue of recognizing them as material evidence, as well as to en-sure the observance of the rights of all participants in criminal proceedings. Materials and methods. The methodological basis includes comparative legal, sociological and psycholog-ical research methods. Judicial practice on these crimes is not widely represented, but is very diverse, therefore, decisions of the courts of first, appellate and cassation instances were used as relevant examples. Results. During the study, the problems of qualification and proof for the category of crimes under consideration were comprehensively considered. Conclusions. The study demonstrates the need to carry out a full range of necessary investi-gative actions at the initial stage of a criminal case investigation. The results of operational-search activities should also be used as an important source of evidence, since through the operational-search activities carried out, it is possible to establish those circumstances that directly affect the qualification of the actions of the guilty person.